PARENTS’ ATTITUDES TOWARDS EARLY MULTILINGUALISM FROM GRADE 1 AND ITS INFLUENCE ON DEVELOPMENT OF KAZAKH LANGUAGE IN MAINSTREAM SCHOOLS - Alimkhanova, Nazerke (Nazarbayev University Graduate School of Education, 2022)
In our world, influenced by globalization, international mobility and the spread of new technologies enhance the importance of learning an international language such as English is undeniable. However, what age could be more appropriate for children to start learning a foreign language, is a concern that students, parents, teachers, and educational authorities raise. In the past decades, there has been a renewed effort to include English in the primary school curriculum in Kazakhstan. The former president of Kazakhstan, Nazarbayev first introduced gradual implementation of teaching English from the primary schools in 2004. Similarly, many schools of the country introduce English from Grade 2 (Zhetpisbayeva, 2016). Since the implementation of the “Trinity of Languages” policy, the Ministry of Education and Science (MoES) of the Republic of Kazakhstan developed a new curriculum in which the starting age for the English language was lowered to six or seven years (Zhetpisbayeva, 2016). There is a concern that implementing English from primary school can negatively affect the development of the national Kazakh language that may even lead to identity loss (Ospanov, 2017). Therefore, this research emphasizes the role of parents as main stakeholders in educational development and aims to explore how primary school parents view learning three languages from Grade 1. In addition, the research also attempts to study the influence of early multilingualism on the development of Kazakh language, as well as exploring the possible benefits and challenges of teaching English from Grade 1. The study employed mixed methods of data collection that included a questionnaire survey and individual interviews with parents. The results of the study show that parents are by and large positive towards early multilingual development of their children. However, parents also preferred gradual introduction of three languages rather than simultaneous implementation of three languages in school curriculum. They believe this will cause various challenges for learners while learning three languages. Also, regarding the influence of early multilingualism on the development of state Kazakh language, parents thought that Russian language could negatively affect the state language acquisition of children as children often receive higher exposure to this language.
Keywords: Type of access: Gated Access; international mobility; globalization; trinity of languages; multilingualism; Research Subject Categories::SOCIAL SCIENCES